Living with brain injury : narrative, community, and women's renegotiation of identity - Stewart, J. Eric (Qualitative studies in psychology, 2014)
"When Nancy was in her late twenties, she began having blinding headaches, tunnel vision, and dizziness, which led to the discovery of an abnormality on her brain stem. Complications during surgery caused serious brain damage, resulting in partial paralysis of the left side of her body and memory and cognitive problems. Although she was constantly evaluated by her doctors, Nancy's own questions and her distress got little attention in the hospital. Later, despite excellent job performance post-injury, her physical impairments were regarded as an embarrassment to the 'perfect' and 'beautiful' corporate image of her employer. Many conversations about brain injury are deficit-focused: those with disabilities are typically spoken about by others, as being a problem about which something must be done. In Living with Brain Injury, J. Eric Stewart takes a new approach, offering narratives which highlight those with brain injury as agents of recovery and change in their own lives. Stewart draws on in-depth interviews with ten women with acquired brain injuries to offer an evocative, multi-voiced account of the women's strategies for resisting marginalization and of their process of making sense of new relationships to self, to family and friends, to work, and to community. Bridging psychology, disability studies, and medical sociology, Living with Brain Injury showcases how--and on what terms--the women come to re-author identity, community, and meaning post-injury. In the Qualitative Studies in Psychology series J. Eric Stewart is a Clinical-Community Psychologist and Associate Professor of Interdisciplinary Arts and Sciences at the University of Washington Bothell"--